2023
DOI: 10.3390/ijms24032995
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Microbiota and Immune Tolerance in Pregnancy

Abstract: Recent studies have demonstrated that the uterus has its own microbiota. However, there is no consensus on endometrial microbiota composition, thus its role in the healthy uterine environment is still a frontier topic. Endometrial receptivity is key to embryo implantation, and in this specific context immunological tolerance against fetal antigens and the tightly regulated expression of inflammatory mediators are fundamental. According to recent evidence, endometrial microbiota may interact in a very dynamic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 111 publications
0
19
0
2
Order By: Relevance
“…Endometrial microbiota is known to play a significant role in pregnancy establishment [19]; however, the specification of the qualitative and quantitative composition of the resident endometrial microorganisms still requires the accumulation of scientific knowledge [2]. In our study, only 9.2% of the endometrium samples did not contain microorganisms, and only 29.2% of the subjects analyzed exerted 1 operational taxonomic unit.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Endometrial microbiota is known to play a significant role in pregnancy establishment [19]; however, the specification of the qualitative and quantitative composition of the resident endometrial microorganisms still requires the accumulation of scientific knowledge [2]. In our study, only 9.2% of the endometrium samples did not contain microorganisms, and only 29.2% of the subjects analyzed exerted 1 operational taxonomic unit.…”
Section: Discussionmentioning
confidence: 60%
“…Both a receptive endometrium and timely signaling between the blastocyst and endometrium determine the success of implantation [17]. For instance, such endometrial factors as calcitonin [18], lysophosphatidic acid (LPA) [19], heparin-binding epidermal growth factor (HB-EGF) [20], leukemia-inhibiting factor (LIF) [21], and epidermal growth factor (EGF) [16] promote embryo implantation. At the same time, the endometrium undergoes remodeling in response to a variety of factors secreted by the embryo, i.e., hCG [6], IL-1 [15], BMP2 [18], IGF1 [20], FGF2 [16], and WNT [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, strategies designed to treat sub-optimal endometrial microbial communities or prevent their formation could improve the endometrial microenvironment and reproductive outcomes. In support of this notion, it has recently been demonstrated in vitro that the probiotic Lactobacillus species, Lactobacillus delbrueckii and Lactobacillus rhamnosus , dampen lipopolysaccharide-induced expression of HLA-DR, CD86, CD80, CD83, and IL-12 from human dendritic cells ( Esmaeili et al , 2018 ), which may suggest a potential mechanism by which microbiota modulate immune-tolerance in early pregnancy ( Inversetti et al , 2023 ). Administration of a live vaginal biotherapeutic, LACTIN-V, containing L. crispatus , has also been shown to reduce the recurrence of bacterial vaginosis and urinary tract infections in non-pregnant women ( Stapleton et al , 2011 ; Cohen et al , 2020 ) and recently was demonstrated to be safe and well tolerated in pregnant women ( Bayar et al , 2023 ).…”
Section: Towards Clinical Translationmentioning
confidence: 93%
“…The mucosa of the reproductive tract can also sense pathogenic bacteria to promote the growth, maturation, and differentiation of immune cells and be engulfed by immune cells; subsequently, immunoactive cells produce immune factors and split target cells to effectively eliminate pathogenic bacteria and maintain epithelial barrier integrity ( Wira et al., 2005 ; Yarbrough et al., 2015 ). When a large number of pathogenic bacteria accumulate in the female reproductive tract, it can disrupt maternal-fetal immune tolerance and induce premature cervical remodeling, ultimately endangering embryo implantation, fetal development and delivery ( Inversetti et al., 2023 ; Elovitz et al., 2019 ). As a consequence, the female reproductive tract harbors a diverse microbial community that exerts a significant influence on its physiological function.…”
Section: Introductionmentioning
confidence: 99%